Evaluation of Preoperative CA15-3 Level and its Relationship with Clinico-Pathological Characteristics in Primary Breast Cancer Patients - Braihan Hamdi Hameed; Izzat Abdulsatar Al-Rayahi; Salwa S. Muhsin (Journal of Techniques)
Cancer antigen15-3 (CA15-3) is utilized as a tumor marker in breast cancer. In the metastatic situation, it has been regarded as having a predictive role. However, the usefulness of serum CA15-3 in preoperative breast cancer remains argumentative. Therefore, this study aimed to estimate the association of preoperative serum CA15-3 level with the clinico-pathological characteristics in Iraqi women patients with breast tumor and their efficiency for the prediction of primary breast cancer. Preoperative CA15-3 levels were assessed by ELISA technique in 60 Iraqi women with breast tumor (30 with primary breast cancer and 30 with benign breast tumor) before surgery and treatment, as well as 30 healthy controls. In addition, the clinico-pathological characteristics information of all the patients was reported. CA15-3 level showed a significant difference between its level in the sera of primary breast cancer women in comparison to the benign breast tumor women (p <0.001) and healthy control women one (p <0.001). The area under the curve (AUC) of CA15-3 for discriminating patients with primary breast cancer and healthy control subjects was 0.720 (95% CI: 0.589 to 0.828). Furthermore, the present study showed that higher preoperative CA15-3 level was significantly associated with a larger tumor size and lymph node metastasis. This means that elevated CA15-3 is correlated with an increased tumor burden, suggesting its predictive value.